Estimating the Direction and Magnitude of Substitution Effects in MLB Event Attendance - Kim, Yong Seog; Moffitt, Clay (International Journal of Engineering and Management Research, 2026)
We estimate the magnitude of the negative impacts (or substitution effects) caused by NHL or NBA games with schedule conflicts on the attendance demand of MLB games. In particular, we aggregate such substitution effects over three different factors such as temporal aggregation factors (e.g., years and days of the week), team aggregation factor (e.g., each MLB team), and team performance aggregation factor (e.g., each MLB team’s performance). Overall, we observe that NHL and NBA games that have schedule conflicts with MLB games more significantly negatively impact the attendance on MLB games during the weekdays (in particular, Thursday and Wednesday) than MLB games during the weekend. We also observe that MLB teams in high standings suffer less from negative substitution effects than MLB teams in low standings in the division. In particular, when MLB teams are in a losing streak, spectators show their deepest disappointments in their teams and avoid to attend MLB games in stadium.